Empowering poor rural Filipinos to nurture equitable climate adaptation - Hellin, Jon; Laborte, Alice; Rosimo, Magnolia; Echavez, Chona; Petesch, Patti; Fisher, Eleanor (International Rice Research Institute, 2025)
The Philippines’s agricultural sector, which plays a crucial role in the country’s food security, is particularly vulnerable to climate-related risks such as cyclones, flooding, drought, and high temperatures. Within this context, there is a pressing need for effective local climate adaptation programs that are informed by and of benefit to vulnerable groups, particularly— although not exclusively—low-income women. Here, a participatory methodology centered around social equity offers vital tools for engaging poor communities who are coping with climate change.